Effectiveness of Self-Technic Behavior Group Counseling Management of Reducing Nomophobia - Risti Ananda Putri; Sigit Sanyata (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study aimed to determine the effectiveness of group counseling behavior self-management techniques to reduce nomophobia in MAN 03 Bener Meriah students. This research was a quasi-experimental quantitative study with a non-equivalent control group design. The population in this study were all students of MAN 03 Bener Meriah. The purposive sampling technique was used because the sample should consist of nomophobic students. Based on this technique, 14 students were determined and divided into two groups, seven students as the control group and the other seven as the experimental group. The nomophobia scale was used as the instrument, while the Wilcoxon signed-rank test was used to analyze the data. The findings showed that self-management techniques in group counseling could reduce nomophobia among students of MAN 03 Bener Meriah. This was evident from the analysis results of the Wilcoxon Signed rank test; the Zcount value was -2.375 b and the Asymp.Sig value. (2-tailed) was 0.018 or probability below alpha 0.05 (0.018 ≤ 0.05), indicating a significant difference between the pretest scores and post-test scores